DAMPAK TERHAMBATNYA PEMBANGUNAN JALAN TOL SEMARANG-DEMAK AKIBAT KEPEMILIKAN TANAH MUSNAH MASYARAKAT: The Impact of Delayed Development of the Semarang-Demak Toll Road Due to the Destruction of Community Land Ownership - Quraisy, Raflinov (Jurnal Globalisasi Hukum., 2024)
Infrastructure development, particularly the Semarang-Demak Toll Road Project, poses serious challenges concerning the procurement of land for public use, especially in the context of unique land characteristics such as degraded land. This study examines legal aspects related to land acquisition within the framework of Indonesia's national agrarian law, including the state's role in ensuring justice and protection of land rights for the community. The issue is analyzed from the perspective of relevant regulations and legal responses to degraded land conditions. The importance of ensuring equal land rights for all citizens is highlighted, in line with the principles of national agrarian law. However, in addressing infrastructure development challenges, particularly concerning land with special characteristics, as seen in the Semarang-Demak Toll Road Project, adaptive regulations are needed. However, in facing the challenges of infrastructure development, especially concerning land with such specific characteristics, adaptive regulations are required. This is reflected in the implementation of special regulations set by the Government, particularly regulating the issue of land acquisition in the context of development for public interest. Research encompasses the differences between general land acquisition mechanisms and mechanisms for addressing social and community impacts on land conditions owned by the community at the project site. Resolving the issues in the project in question relies not only on legal regulations but also requires good collaboration and coordination between policymakers and the community.